DEPOLIMERISASI LIMBAH POLIETILEN TEREFTALAT (PET) MENJADI ASAM TEREFTALAT (SUMBER LINKER MOF-5) DENGAN METODE HIDROLISIS ASAM BASA - Mid, Arsy Aprilia; Syaima, Husna; Hindryawati, Noor (PROSIDING SEMINAR KIMIA, 2024)
Terephthalic acid is an important ligand in the manufacture of MOF-5 which has been obtained from the depolymerization of PET (polyethylene terephthalate) recycled from PET plastic waste. Depolymerization of PET polymers into terephthalic acid ligands (linkers) is carried out using the acid-base hydrolysis method at room temperature using H2SO4 and NaOH. The yield was obtained at 40.95% (8.19 grams). PET monomers in the form of terephthalic acid were then tested by Thin Layer Chromatography (TLC) using n-hexane and ethyl acetate solvents (1:2). The TLC results showed the same stain spot between depolymerized terephthalic acid and commercial terephthalic acid. Depolymerized terephthalic acid and commercial terephthalic acid were then analyzed using Fourier Transform Infrared (FTIR) which showed the presence of functional groups C=O, C-O, C-H, and O-H and analyzed with a UV-Visible Spectrophotometer and obtained a maximum wavelength in both materials of 306 nm. Keywords: Terephthalic Acid, depolymerization, polyethylene terephthalate